PERLINDUNGAN HAK KONSUMEN ATAS JASA PENYEDIAAN AIR OLEH PERUMDA AIR MINUM DANUM TAKA DI PENAJAM PASER UTARA, KALIMANTAN TIMUR: Protection Of Consumer Rights To Water Supply Services By Perumda Air Minum Danum Taka In Penajam Paser Utara, East Kalimantan - Amira Wristy Mutiah; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2025)
The community has the right to use water as regulated in Article 8 of Law No. 17 of 2019 concerning Water Resources. One of the government's efforts to manage water resources in Penajam Paser Utara Regency, East Kalimantan is by forming Perumda Air Minum Danum Taka. Of course, in managing the clean water, Perumda Air Minum Danum Taka refers to Permenkes No. 2 of 2023 concerning Implementation Regulations of Government Regulation No. 66 of 2014 concerning Environmental Health. Despite these regulations, the public often complains about the unfit quality of clean water, so that consumer rights in Article 4 of Law No. 8 of 1999 concerning Consumer Protection are not fulfilled. So the identification problem that arises is how the protection of consumer rights due to losses experienced due to the lack of clean water quality provided by Perumda Air Minum Danum Taka. The results and conclusion of this study state that consumer protection provided by Perumda Air Minum Danum Taka has not been carried out optimally. Efforts that can be made by consumers are by settlement through BPSK or filing a class action lawsuit, in accordance with Article 45 Paragraph (1) of the Consumer Protection Law.